WIRETAPPING ON SUBMARINE COMMUNICATIONS CABLE: QUESTIONING ITS LEGALITY AMIDST LONG STANDING PRACTICE - Hafidz L. Botua; Chloryne Trie Isana Dewi; R. Achmad Gusman Catur Siswandi (Padjadjaran Journal of International Law, 2022)
Up to 95% of the communication infrastructures are currently served by the submarine communications cable networks, which in their utilisation connect a wide variety of communications data. The increasingly advanced infrastructure is in fact unable to go hand in hand with legal transformation. At the present time, international law provides only partial protection in form of prevention against damage to the cable networks. Consequently, in the event that data transmissions across the cable networks are illegally exploited by foreign parties through "wiretapping" without inflicting any damage, as long as it is committed in the body of waters outside the state's sovereignty, the international law is unable to explicitly address this situation. The wiretapping has occurred in a couple of instances, however, the proper preventive measures are still in question. Fortunately, the most recent practice of international law in the field of human rights has provided some clarities through case law. Despite the fact that it has only been applied regionally, this endeavour is at the very least capable of supporting future proposed legal reforms. This article will further elaborate on the legality of wiretapping on submarine communications cable networks based on the relevant field of international law, which eventually revealed that such conduct is contrary to cyber law, international law of the sea and human rights law.